The Theory of Multiple Intelligences and Its Implications for Islamic Religious Education Learning - Aziza, Nur; Sirozi, Muhammad (FKIP - Universitas Riau, 2025)
This study examines the application of Howard Gardner's Multiple Intelligences (MI) theory to Islamic Religious Education (PAI) learning in Indonesia. MI theory asserts that intelligence consists of various types, such as linguistic, logical-mathematical, visual-spatial, musical, kinesthetic, interpersonal, intrapersonal, and naturalistic. The research method used was a qualitative literature study approach, analyzing literature related to the integration of MI in Islamic Religious Education (PAI) learning to develop students' holistic potential. The results show that the application of MI enables teachers to design more varied, interactive, and student-centered learning, tailored to individual learning styles. However, obstacles remain, such as limited teacher understanding and pedagogical skills and an education system that emphasizes cognitive outcomes over affective and psychomotor aspects. Therefore, continuous teacher professional development, the provision of creative learning tools, and a more comprehensive assessment system are needed. Overall, the application of MI theory in PAI contributes significantly to increased learning motivation, character development, and spiritual awareness among students, making religious education more meaningful, enjoyable, and contextualized in everyday life.